A Predator-prey Model with Allee Effect in Patch Environment - LI Meng; CHANG Xiao yuan (Journal of Harbin University of Science and Technology)
In order to study the dynamics of the predator-prey model with Allee effect in two patch environments, the effects of diffusion on the population in two patch environments are analyzed. The positivity and the ultimate boundedness of the solutions are obtained , also the existence and the stability of the equilibrium points are proved. It is concluded that when the diffusion coefficient is large enough, the equilibrium points are unstable. However, when the diffusion coefficient is small enough, there are two equilibrium points which are both locally asymptotically stable, which phenomenon is caused by the Allee effect in this model. Finally, the numerical simulations are carried out to verify the obtained results.